2005
DOI: 10.1523/jneurosci.5060-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 Inhibits Extracellular Signal-Regulated Kinase to Promote Neuronal Survival via the Phosphatidylinositol 3-Kinase/Protein Kinase A/c-Raf Pathway

Abstract: Extracellular signal-regulated kinase (ERK) activation has been shown to promote neuronal death in various paradigms. We demonstrated previously that the late and sustained ERK activation in cerebellar granule neurons (CGNs) cultured in low potassium predominantly promotes plasma membrane (PM) damage. Here, we examined the effects of a well established neuronal survival factor, insulin-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 76 publications
5
51
1
2
Order By: Relevance
“…The specificity of LY-2949002 on PI3-K activity was further confirmed by the lack of rescue effect observed with IGF-I, a growth factor that predominantly signals through PI3-K in granule neurons (Fig. 4) (D 0 Mello et al 1997;Yamagashi et al 2003;Subramaniam et al 2005).…”
Section: Bzatp Protects Granule Neurons From Apoptosis Induced By Pi3mentioning
confidence: 76%
“…The specificity of LY-2949002 on PI3-K activity was further confirmed by the lack of rescue effect observed with IGF-I, a growth factor that predominantly signals through PI3-K in granule neurons (Fig. 4) (D 0 Mello et al 1997;Yamagashi et al 2003;Subramaniam et al 2005).…”
Section: Bzatp Protects Granule Neurons From Apoptosis Induced By Pi3mentioning
confidence: 76%
“…More recently, we showed that intranasal administration of rhIGF-1 for 2 weeks, in order to promote IGF-1 delivery to the brain, enhanced IGF-1 cortical levels and improved motor activity and both peripheral and central metabolic abnormalities in YAC128 mice [30], an animal model presenting high levels of IGF-1 in plasma and expression in the striatum [26]. We also showed that rhIGF-1 intranasal administration in YAC128 mice activated [87]. Also, insulin was shown to inhibit Erk1/2 phosphorylation in a PI-3K-dependent manner in Neuro2a cells [88].…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, hemoglobin might exist in non-erythroid cells and fulfill alternative function. Akap1 encodes an anchoring protein widely expressed in brain (McKee et al 2005) and crucial for cAMP/PKA signaling (Newhall et al 2006), a pathway which mediates the anti-apoptotic activity of IGF1 on cerebellum granular neurons (Subramaniam et al 2005). The downregulation of cdh1, encoding E-cadherin, should also influence granular cell cycling and differentiation (Almeida et al 2005).…”
Section: Discussionmentioning
confidence: 99%